Potential of corn cob compost in corn fertilization on alfisol soil - Purnomo Djoko; Setyaningrum Desy (BIO Web of Conferences)
Corn cobs as waste material after the seeds are removed have not been utilized so they have the potential to become pollutants. Alfisols as marginal land require improvement materials for cultivated land. The study aims to examine the potential of corn cob compost on the growth and yield of corn on alfisol soil. The study used a Randomized Block Design with a single factor, namely treatment with six levels, namely inorganic fertilizer (doses of 350, 125, and 100 kg.ha-1) and corn cob compost with doses of 2.5; 5.0; 7.0; 10.0; 12.5 tons.ha-1. Repeated three times. The application of corn cob compost did not differ from the application of inorganic fertilizers on the number of cobs (fruit.m-2), seed weight (g.m-2), chlorophyll a, b, and total content (μgg-1). The inorganic fertilizer treatment showed the highest seed weight of 550.2 kg.ha-1. Corn cob compost dose of 7.5 tons.ha-1 increases the number of cobs per m2, weight of 100 seeds, number of seeds per m2. Corn cob compost has the potential to replace inorganic fertilizers in corn cultivation on Alfisol soil.